An analysis of the meaning constructed by woman gaze through cinematic instruments in Yeşim Ustaoğlu’s film Clair Obscur (2016) - Beril Uğuz (ARTS: Artuklu Sanat ve Beşeri Bilimler Dergisi)

(untitled)
Although the woman gaze concept in cinema has not yet been clearly defined in the academic literature, it refers to the gaze, perspective, voice, subjectivity, experiences, and inner world of the woman director and the woman character. The aim of this study is to contribute to the definition of this concept by investigating the tools through which meaning is constructed via the woman gaze in cinema. To this end, the film Clair Obscur (Tereddüt, 2016), directed by Yeşim Ustaoğlu, which focuses on the viewpoints, and experiences of women characters, is examined through textual film analysis with a holistic approach. According to the findings, in Clair Obscur, the subjectivities of women characters are prioritized through different cinematographic, editing, and mise-en-scène tools. The film distinguishes itself from mainstream cinema codes with its disturbing thematic narrative. Consequently a definition for the construction of meaning through the woman gaze in cinema can be mentioned.